SEBARAN SPASIAL SPESIES POHON DOMINAN DI KAWASAN HUTAN WORNOJIWO, KEBUN RAYA CIBODAS - Hidayat Syamsul (Media Konservasi, 2014)
Wornojiwo is one of the remnant forest areas located within Cibodas Botanical Garden. Some important native plants peciesoccur in this area are representing the sub montane vegetation of Mount Gede Pangrango. Their occurrence needs to be investigated in order to establish a proper conservation management. The existenceof a speciesis basically determined by the spatial distribution patterns within the community. Spatial distribution of dominant species are very important to set up a long term conservation strategy. Square samplings were performed in this study to asses plant species richness and abundance and were used as a bases for determining species distribution patterns. The variance ratio and frequency distribution of five dominant species were analysed, showing that Ficus ribes had a homogeneous or regular distribution, Macropanax dispermum possessed a grouped pattern, Ostodes paniculata spreaded randomly, while Villubrunea rubescens and Castanop sisargentea occurred homogeneously. Keyword: Dominant species, Frequency distribution, Remnant forest, Spatial pattern, Variance ratio.